De la exhumación a la monumentalización : una perspectiva interdisciplinar sobre la legitimación política en España desde el año 2000 - Daniel Palacios González; Miriam Saqqa Carazo (Amnis)
This text aims to introduce the experience of exhumations and monumentalization of the mass graves of the Spanish Civil War, understanding them as a tool for political legitimation, used recurrently since 2000. The two fundamental facets that will be addressed are exhumation as a tool for legitimisation through the discourse of human rights, and monumentalisation as a tool for legitimisation through the discourse of democratic tradition. Thus, these two rhetorics, that of the recovery of a democratic memory and that of human rights, will determine the character of political legitimacy in the two selected objects of study.